Fate‐mapping analysis of cochlear cells expressing Atoh1 mRNA via a new Atoh13*HA‐P2A‐Cre knockin mouse strain. Issue 7 (25th January 2022) - Li, Shuting; Fan, Ting; Li, Chao; Wang, Yunfeng; Li, Jian; Liu, Zhiyong
Abstract: Background: Atoh1 is recognized to be essential for cochlear hair cell (HC) development. However, Atoh1 temporal and spatial expression patterns remain widely debated. Here, we aimed to obtain evidence to resolve the controversies regarding Atoh1 expression by generating a new knockin mouse strain: Atoh1 3*HA‐P2A‐Cre . Results: Fate‐mapping analysis of Atoh1 3*HA‐P2A‐Cre/+ ; Rosa26 ‐CAG‐LSL‐tdTomato (Ai9)/+ mice enabled us to concurrently characterize the temporal expression of Atoh1 protein (through HA‐tag immunostaining) and visualize the cells expressing Atoh1 mRNA (as tdTomato+ cells). Our findings show that whereas Atoh1 mRNA expression is rapidly turned on in early cochlear progenitors, Atoh1 protein is only detected in differentiating HCs or progenitors just committed to the HC fate. Cre activity is also stronger in Atoh1 3*HA‐P2A‐Cre/+ than in previous mouse models, because almost all cochlear HCs and nearby supporting cells here are tdTomato+. Furthermore, tdTomato, but not HA, is expressed in middle and apical spiral ganglion neurons. Conclusion: Collectively, our findings indicate that Atoh1 3*HA‐P2A‐Cre can serve as a powerful genetic model in the developmental biology field. Key Findings: Atoh1 mRNA is expressed in cochlear hair cells, supporting cells and spiral ganglion neurons. Atoh1 protein is only detected in cochlear hair cells, suggesting that it is a hair cell fate selecting factor. Atoh1‐3*HA‐P2A‐Cre/+ strain has a high Cre activity. Atoh1 expression is intact in homozygotes of Atoh1‐3*HA‐P2A‐Cre that do not have apparent hearing defects.